(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aimed to measure the degree of practicing persisting by the basic fourth graders in Science, and to investigate the impact of sex on this practicing, and its relationship with the critical thinking. To achieve that, the researcher used the descriptive approach, and prepared a measure of persisting, and another for critical thinking skills, as it was ascertained validity and reliability, and distributed to a sample of (135) students of the basic fourth graders in official schools at Tartous city. The results showed that the research sample practice persisting in a high degree, and that female students possess persisting equally owned by male students, and the results showed a strong, positive and statistically significant correlation between persisting and critical thinking. The researcher suggested the establishment of educational programs for the development of persisting among basic educational students in general, and basic fourth graders students in particular. هدف هذا البحث إلى تعرّف درجة ممارسة المثابرة كعادة عقلية في مادة العلوم لدى تلاميذ الصف الرابع الأساسي في مدارس مدينة طرطوس الرسمية، وأثر النوع على هذه الممارسة، وعلاقتها مع التفكير الناقد. ولتحقيق ذلك، استخدم المنهج الوصفي، وأعدّت الباحثة مقياساً للمثابرة وآخر لمهارات التفكير الناقد، إذ تم التأكد من صدقهما وثباتهما، ووزّع المقياسان على عينة قوامها (135) تلميذاً وتلميذةً من تلاميذ الصف الرابع الأساسي في مدارس مدينة طرطوس الرسمية. وأظهرت النتائج أن عينة البحث تمارس المثابرة كعادة عقلية بدرجة مرتفعة، وأن التلميذات الإناث يمتلكن عادة المثابرة بالدرجة نفسها التي يمتلكها التلاميذ الذكور، كما بينت النتائج وجود علاقة ارتباطية موجبة قوية ودالة إحصائياً بين المثابرة والتفكير الناقد. واقتُرح تقديم برامج تربوية وتعليمية لتنمية المثابرة لدى تلاميذ مرحلة التعليم الأساسي بشكلٍ عامٍّ، وتلاميذ الصف الرابع الأساسي بشكلٍ خاصٍّ.